Analysis of legal protection for victims of illegal investment of ponzi schemes - Jestyn Hermawan; O.K. Isnainul; Elvira Fitriyani Pakpahan; Heriyanti (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2023)
Technological development connects the world and becomes the basis for digitalizing finance and boosting the economy. Investment is useful for protecting investors from inflation, planning for the future economy, increasing wealth, and providing convenience in emergency needs. This study aims to analyze legal protection, the problem, and the consequences of law enforcement toward corporations. This study used the library research method. This study used a normative juridical approach which means that the study concerns norms, legislation, and court decisions related to legal protection for victims of illegal investment. The result of the study showed that the court has provided legal protection but it has not been able to meet the aspect of justice. Indonesia faced some problems in enforcing the law and maximizing the function of government institutions. This is proven by the great power to deceive using current developments. Besides, the results reveal that the court gave punishment as the result of the law enforcement to the corporation such as company dissolution and compensation payment to the victim.